Conectividad en tiempos de pandemia en el adulto mayor Centro Gerontológico Santa Gema de Galgani - Macías Cedeño , María Alejandra (2021)
Connectivity linked to technology and the COVID -19 pandemic has brought drastic changes in our lives. The most momentous change has been the migration of activities of daily life to the digital world. These activities are related to education, recreation, work, social encounters, and leisure, among others. This variation affects the ability to adapt in the population, especially in older adults. Considering the aforementioned problem, this work aims to analyze how connectivity in times of pandemic affects older adults. To develop this project, a non-experimental quantitative research was carried out using the interview technique, with a simple descriptive design. The sample consisted of 50 older adults participating in the services provided by the Santa Gema de Galgani Gerontological Center of the rural parish Abdón Calderón and a question bank was used as an instrument. Obtaining as a result that residing in a rural area does not allow older adults to have the necessary connectivity service that they must to be able to access the virtual platforms and thus be participants in the activities issued by the Center where they partook in person before the pandemic. As a conclusion it can be said that not only connectivity is the only impediment, at the same time not having a technological device and not knowing how it works, separates them from the benefits offered by joint connectivity to technology, which cause effects on their emotional state.